2015
DOI: 10.1155/2016/4323198
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Levels of Urinary Markers of Oxidative DNA and RNA Damage in Type 2 Diabetes with Complications

Abstract: The mechanisms underlying progression of type 2 diabetes are complex and varied. Recent studies indicated that oxidative stress provided a new sight. To further assess the relationship between nucleic acid oxidation and complications in patients with type 2 diabetes and explore its possible molecular mechanisms, we studied 1316 subjects, including 633 type 2 diabetes patients and 683 age- and sex-matched healthy controls. Urinary levels of DNA oxidation marker 8-oxo-7,8-dihydro-2′-deoxyguanosine (8-oxodGuo) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 41 publications
0
35
0
Order By: Relevance
“…diabetes is supported by evidence from animal models, and 8-oxoGuo has been found to be a more sensitive nucleic acid marker of diabetes morbidity and mortality than 8-oxodG (28). Moreover, a cross-sectional study indicated notably higher 8-oxoGuo levels in patients with type 2 diabetes with diabetic macrovascular complications, as well as higher 8-oxodG levels (although to a lesser extent) (29).…”
Section: Discussionmentioning
confidence: 91%
“…diabetes is supported by evidence from animal models, and 8-oxoGuo has been found to be a more sensitive nucleic acid marker of diabetes morbidity and mortality than 8-oxodG (28). Moreover, a cross-sectional study indicated notably higher 8-oxoGuo levels in patients with type 2 diabetes with diabetic macrovascular complications, as well as higher 8-oxodG levels (although to a lesser extent) (29).…”
Section: Discussionmentioning
confidence: 91%
“…Again, we can refer the previous diabetic microvascular complications to the oxidative damage that happens when the ROS level overpowers defensive mechanisms, leading to a cellular imbalance between pro-and antioxidant factors [32]. Elevated levels of oxidation markers such as 8-oxodG most likely prompt to strand breaks and oxidative base changes; and multiple signaling pathways that may likewise add to the unfavorable impacts of glucotoxicity on cellular functions [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…OS‐induced damage to DNA also contributes to neurodegeneration, promoting Parkinson's disease, Alzheimer's disease, and sporadic amyotrophic lateral sclerosis . Other health disorders arising from oxidative damage to DNA are cardiovascular diseases, Wilson's disease, Huntington's disease, inflammatory bowel disease, acquired immunodeficiency syndrome, diabetes and its complications, chronic obstructive pulmonary disease, and rheumatoid arthritis …”
Section: Introductionmentioning
confidence: 99%
“…6 OS-induced damage to DNA also contributes to neurodegeneration, promoting Parkinson's disease, [7][8][9] Alzheimer's disease, [10][11][12] and sporadic amyotrophic lateral sclerosis. 13 Other health disorders arising from oxidative damage to DNA are cardiovascular diseases, [14][15][16][17] Wilson's disease, 18,19 Huntington's disease, 20,21 inflammatory bowel disease, 22,23 acquired immunodeficiency syndrome, 24,25 diabetes 26 and its complications, [27][28][29] chronic obstructive pulmonary disease, 30 and rheumatoid arthritis. [31][32][33] The hydroxyl radical (˙OH) has been held responsible for the most common oxidative damage to DNA, 34,35 which involves different chemical routes and yields diverse products (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%